Metabolic signatures of genetically elevated vitamin D among Chinese: observational and Mendelian randomization study - Zhuang, Z; Yu, C; Guo, Y; Bian, Z; Yang, L; Millwood, IY; Walters, RG; Chen, Y; Xu, Q; Zou, M; Chen, J; Chen, Z; et al. (Oxford University Press, 2021)
Context Observational studies have suggested that higher circulating 25-hydroxyvitamin D [25(OH)D] levels are associated with favorable serum lipids and related metabolites. However, whether such observations reflect causality remains unclear.